Усовершенствование конструкции генераторов для ветроустановки с аэродинамической мультипликацией - Панченко, Виктор Иванович; Цыпленков, Дмитрий Владимирович; Кириченко, Марина Сергеевна; Федоров, Сергей Иванович; Гребенюк, Андрей Николаевич (НТУ "ХПИ", 2016)
В работе рассмотрены пути улучшения массогабаритных показателей генераторов для ветроустановок с аэродинамической мультипликацией и пути уменьшения массы и стоимости обмоток. Предлагается для улучшения свойств генераторов, которые устанавливаются на лопастях ветроэлектрической установки (ветроустановка с аэродинамической мультипликацией) часть зубцов статора выполнить скошенными с размещением на них обмотки подмагничивания. Предложено решить проблему бесконтактности токосъема с генераторов за счет применения трехфазной асинхронной машины с фазным ротором.

Wind-driven power plants with both horizontal and vertical axis of rotation of wind wheel are usually slow-speed. Therefore used generators are multipole performed to provide a standard frequency of output voltage that leads to a noticeable increase in weight and size of wind turbines. To reduce the weight of generator and to refuse from the use of mechanical multipliers is possible by means of placement of the generators on the blades of the main turbine, usually three-bladed, at some distance from its axis (wind turbine with a dynamic multiplication). Auxiliary wind wheels of small diameter are fixed at the ends of the generator shafts. They are streamlined by ram air flow whose speed is much greater than atmospheric one, causing the rotation of the main wind wheel. As a result, the auxiliary wind wheels will have a considerable frequency of rotation, which allow the use of high-speed electric generators. Taking into account the location of these generators, the basic requirements for their construction are as follows: the minimum specific weight and high operation reliability. Furthermore, possibility of output voltage regulation of generators and their low cost should be provided. There have been proposed the improvement ways of weight and size of generators for wind turbines with aerodynamic multiplication and ways to reduce the weight and cost of the windings. It is proposed the part of stator teeth perform beveled with placing on them the field winding to improve the properties of generators, which are installed on the blades of a wind-driven power plant. It is proposed to solve the problem with the contactless current collection from generators through the use of three-phase asynchronous machine with wound rotor.
Improving the generators design for wind turbine with aerodynamic multiplication
Keywords: ветроустановка; аэродинамическая мультипликация; синхронный генератор; обмотка статора; асинхронная машина; фазный ротор